Locke's Philosophical Ideas on Education - Cabello, Arturo Lucas (2020)
This paper tries to analyze the ideas about education that the philosopher of the tabula rasa, John Locke, proposed towards the middle of the 17th century. According to him, education must be based more on virtue and moral values than epistemic education, since men are good or bad, useful or not, because of the education they receive from the family or school. A concern for its quality spreads throughout our educational system, a problem that for Locke was already central, since he said that if we want the common good, it is necessary to have talented teachers who are solidly educated in moral qualities. Locke's pedagogy can serve as a propaedeutic framework to reflect on the great fractures of our educational system, and to propose a sustainable and inclusive education.